Microvascular Dysfunction in Patients With Type II Diabetes Mellitus: Invasive Assessment of Absolute Coronary Blood Flow and Microvascular Resistance Reserve - Gallinoro, Emanuele; Paolisso, Pasquale; Candreva, Alessandro; Bermpeis, Konstantinos; Fabbricatore, Davide; Esposito, Giuseppe; Bertolone, Dario; Fernandez Peregrina, Estefania; Munhoz, Daniel; Mileva, Niya; Penicka, Martin; Bartunek, Jozef; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background Coronary microvascular dysfunction (CMD) is an early feature of diabetic cardiomyopathy, which usually precedes the onset of diastolic and systolic dysfunction. Continuous intracoronary thermodilution allows an accurate and reproducible assessment of absolute coronary blood flow and microvascular resistance allowing the evaluation of coronary flow reserve (CFR) and Microvascular Resistance Reserve (MRR), a novel index specific for microvascular function. In this study we compared absolute coronary flow and resistance, CFR and MRR assessed by continuous intracoronary thermodilution in diabetic versus non-diabetic patients. Methods In this observational retrospective study, 108 patients with suspected angina and non-obstructive coronary artery disease (NOCAD) consecutively undergoing elective coronary angiography (CAG) from September 2018 to June 2021 were enrolled. The invasive functional assessment of microvascular function was performed in the left anterior descending artery (LAD) with intracoronary continuous thermodilution. Patients were classified according to the presence of diabetes mellitus (DM). Absolute resting and hyperaemic coronary blood flow (in mL/min) and resistance (in WU) were compared between the two cohorts. CFR and MRR were calculated to assess microvascular function. Left atrial reservoir strain (LASr) was also compared between the two study groups. Results The median FFR value was 0.83 [0.79-0.87] without any significant difference between the two groups. Absolute resting and hyperemic flow in the left anterior descending coronary were similar between diabetic and non-diabetic patients. Similarly, resting and hyperemic resistances did not change significantly between the two groups. In the DM cohort the CFR and MRR were significantly lower compared to the control group (CFR = 2.38 ± 0.61 and 2.88 ± 0.82; MRR = 2.79 ± 0.87 and 3.48 ± 1.02 for diabetic and non-diabetic patients respectively, [p<0.05 for both]). Likewise, diabetic patients had a significantly lower reservoir, contractile and conductive LAS (all p < 0.05). Conclusions CFR and MRR were significantly impaired in patients with DM. The lower LASr in the diabetic cohort may reflect a subclinical diastolic dysfunction linked to the CMD. Continuous intracoronary thermodilution-derived indexes provide a reliable and operator-independent assessment of coronary macro- and microvasculature and might potentially facilitate widespread clinical adoption of invasive physiologic assessment of suspected microvascular disease.